Is India’s Manufacturing Sector Moving Away from Cities? - Ghani, Ejaz; Goswami, Arti Grover; Kerr, William R. (World Bank, Washington, DC, 2013)
This paper investigates the urbanization of the Indian manufacturing sector by combining enterprise data from formal and informal sectors. It finds that plants in the formal sector are moving away from urban and into rural locations, while the informal sector is moving from rural to urban locations. Although the secular trend for India's manufacturing urbanization has slowed down, the localized importance of education and infrastructure has not. The results suggest that districts with better education and infrastructure have experienced a faster pace of urbanization, although higher urban-rural cost ratios cause movement out of urban areas. This process is associated with improvements in the spatial allocation of plants across urban and rural locations. Spatial location of plants has implications for policy on investments in education, infrastructure, and the livability of cities. The high share of urbanization occurring in the informal sector suggests that urbanization policies that contain inclusionary approaches may be more successful in promoting local development and managing its strains than those focused only on the formal sector. Cities are evolving in India from places of goods production to forges of human capital and coping mechanisms for survival.